THE LINK BETWEEN THE PRESENCE OF AN ODONTOGENIC RADICULAR CYST AND THE BODY S IMMUNE RESPONCE -CASE REPORT - Stojanova, Irena; Dimitrovski, Oliver; Stevkovska, Daniela Veleska; Arsovska, Mirjana Markovska; Spirov, Vancho (Journal of Morphological Sciences; Vol 5 No 1 (2022): JMS, 2022)
Odontogenic radicular cysts are the most common odontogenic inflammatory cysts. Immunopathological reactions play a dominant role in their etiopathogenesis. This study aimed to determine the presence of T and B lymphocytes, cells in the inflammatory infiltrate and, the impact of the cystic lesion on the systemic immune response by verifying the changes in the immune system by applying the immunohistochemical method in a patient with a residual cyst in the lower jaw. and one month after surgery. Case Report: A 60-year-old woman with a residual cyst in her lower jaw was admitted to the Oral Surgery Clinic. Immunoassay of blood was performed to determine the values of immunoglobulins IgA, IgG and Ig M before surgery, cyst enucleation in toto, pathohistological and immunohistochemical analysis of CD3, CD4, CD8, CD20, and CD68 markers. Immunological blood tests were performed one month after surgery. Pathohistological and immunohistochemical analysis confirmed the diagnosis of radicular (residual) cyst in the mandible with the presence of multilayered squamous epithelium beneath which is an inflammatory infiltrate with granulation tissue and deposited cholesterol crystals with predominant lymphadenopathy of predominant lymphadenopathy. %), are dominated by macrophages and histiocytes. Serum immunoglobulin IgA, Ig G, and IgM levels were reduced after surgery. The use of pathohistological and immunohistochemical analyzes proves the presence of cellular and humoral immune responses and their role in the etiopathogenesis and development of cysts, while immunoassays confirm the presence of human immunoglobulin this suggests the importance of early detection and therapeutic approach to radicular cysts. Keywords : residual cyst, pathohistological, immunohistochemical and immunological analysis, human immune response. https://doi.org/10.55302/JMS2251145s